Analysis of Table Tennis Backhand Drive Technique Skills in Extracurriculars Students at Senior Hights School 5 Lubuklinggau - Arianta, Indra; Lian, Bukman; Lanos, Muhsana El Cintami (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine the results and analyze the ability of backhand drive techniques in students who take part in extracurricular table tennis at SMA Negeri 5 Lubukinggau. This study is quantitative descriptive research. The research sample amounted to 16 students who participated in extracurricular table tennis at SMA Negeri 5 Lubuklinggau, from this study the results were obtained namely the ability to hit backhand drives with the category “very good” numbered 0 people with a percentage of 0%, in the category “good” amounted to 2 people with a percentage of 12.50%, in the category “medium” amounted to 4 people with a percentage of 25%, in the theory of “less” there were 8 people with a percentage of 25%, while the “very less” category consists of 2 people with a percentage of 2.50%, thus it can be concluded that the results of backhand drive hitting ability in students who take part in extracurricular table tennis at SMA Negeri 5 Lubuklinggau are in the “less” category with average results of 25.68.